Utilization of Herbal Plants in Increasing Hemoglobin Levels - Atika Zahria Arisanti, savira dian safitri; Savira Dian Safitri (Jurnal Ilmu Kesehatan (JIKSAN), 2025)
Background: Anemia is a complex and prevalent health problem among Indonesian women, particularly during pregnancy. The most common cause of anemia in pregnancy is nutritional deficiency, which can negatively impact maternal and fetal health. Non-pharmacological treatments have become an alternative approach to increase hemoglobin (Hb) levels with minimal side effects, as they utilize natural ingredients traditionally known to improve nutritional status. Green beans, honey, and dragon fruit are examples of natural products commonly used to help prevent and treat anemia. Purpose: This scientific paper aims to analyze the effect of administering green bean juice and honey on increasing hemoglobin levels in pregnant women with anemia. Method: A literature review was conducted by searching national and international publications through various databases and platforms. Keywords were structured using the PICO formula to identify relevant studies on non-pharmacological interventions to improve hemoglobin levels during pregnancy. Results: The analysis showed that the administration of herbal plants, particularly green bean juice combined with honey, is effective in increasing hemoglobin levels among pregnant women with anemia. This positive effect is attributed to the high iron content found in green beans and the nutritional support provided by honey. Therefore, the consumption of these natural products can be recommended as an additional dietary strategy to help increase hemoglobin levels safely and effectively in pregnant women.